“The Machina Telephonica and its Sudden God” - Om telefonen i Lolita - Nyegaard, Ole (Passage - Tidsskrift for litteratur og kritik, 2014)
Ole Nyegaard: “‘The Machina Telephonica and its Sudden God’: The Telephone in Lolita” This article looks at the telephone as a literary motif deployed by Marcel Proust and Vladimir Nabokov. In The Guermantes Way, Proust takes the reader back to the early days of the telephone and recreates the awe of experiencing the dissociation of the speaker from the voice. Proust’s telephone scene carries a contrast between hyperbolic religious imagery and profane interruption with humorous effect. In Lolita the tables are turned. Humbert presents himself as an aesthetic übermensch; the good reader, however, may see him as a solipsist. The telephone becomes a quotidian deus ex machina which bursts Humbert’s bubble of self-absorption.